PENERAPAN METODE INTEGRATIF UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS CERITA PENDEK PADA SISWA KELAS IX DI SMP NEGERI 15 BANDUNG - Firda Amellia Fitrian, - (2022)
This research is motivated by problems in the ability to write short story texts, namely, the absence of student interest in writing learning. Therefore, this study aims to improve the ability to write short stories for grade 9 students. This study used the Kemmis and Mc. Taggart model PTK method with two learning cycles. The learning in this study uses an integrative method with the help of Podcast media as a means of inspiring students to write short story texts. The results of this study show an increase in scores in the aspects of the suitability of the title with the content, the integration of short story elements, the completeness of the structure of short stories, the suitability of the use of the linguistic aspects of short stories, and the suitability of short story writing with KBBI and PUEBI from cycle 1 to cycle 2. The average value of the aspect of conformity of the title to the content increased from a score of 68.18 to 73.48; the aspect of the integration of short story elements increased from a score of 81.06 to 82.58; the completeness aspect of the structure of the short story increased from a score of 81.06 to 84.09; the conformity aspect of the use of the linguistic aspect of the short story increased from a score of 58.33 to 59.09; and the conformity aspect of short story writing with KBBI and PUEBI increased from a score of 48.48 to 57.58. Based on the results of the study, it can be concluded that students' ability to write short story texts can be improved through learning with integrative methods.